Optimized structure of sowing areas and crop rotation for the piedmont zone of the NOR-Alanya - D. M. Mamiev; A. A. Abaev; A. A. Tedeeva (Новые технологии)
The article considers an optimized structure of sowing areas, taking into account specific agro-climatic conditions for the foothill zone of the North Ossetia Republic-Alania. Field (grass and corn-grass), fodder and vegetable crop rotations based on the improved structure of sown areas have been developed, allowing the introduction of intercrop cultures with the simultaneous increase of soil fertility.